Inovatif Music: Baksya Nirleka | Musik Inovatif: Baksya Nirleka - Komang Lanang Adi Arimbawa; Hendra Santosa (GHURNITA: Jurnal Seni Karawitan, 2024)
Baksya Nirleka's innovative musical work describes the interaction of primitive humans who did not know how to write (praaksara). Baksya Nirleka's work was realized using express media, materials available around him, and existing media such as Balinese gamelan, which was chosen by several instruments believed to support this work. The problem that will be discussed is the form and process of creating Baksya Nirleka's innovative musical work. The author aims to highlight primitive humans in Baksya Nirleka's work because of their creativity in using materials around them as tools for interacting with each other because primitive humans are still dependent on nature. The method that the author used in preparing this work is the Alma M. Hawkins Method, which consists of 3 stages: Exploration Stage (exploration), Improvisation Stage (experimentation), and Forming Stage (formation). Baksya Nirleka's work consists of 4 parts, and each part has a different depiction.